THE STRENGTHENING OF CHARACTER EDUCATION BASED ON LOCAL WISDOM THROUGH HIKAYAT NYIMAS GAMPARAN - Haryanti, Ade Siti; Hufad, Achmad; Leksono, Suroso Mukti (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
This study describes character education in developing the affective domain for students, especially for junior high school students. Important character education is instilled in junior high school children who are intensively looking for identity, this character education is expected to form students who have morals and noble character in accordance with the 2013 curriculum. Teachers can develop subject matter through a local wisdom approach, which is owned by the area. One of the local wisdoms in Balaraja is the saga Nyimas Gamparan, which is packaged in an interesting picture story book. So the benefits of this study are; 1) Providing creative and innovative ideas for teachers in developing learning materials based on local wisdom through the saga of Nyimas Gamparan; 2) Motivating schools, teachers, parents, and the community to direct students who have positive attitudes towards the surrounding culture; and 3) motivate students in the formation of characters that will be useful in their lives.